2008
DOI: 10.1128/jvi.00605-08
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Plasma (TRAIL), TNFR-2, Fas Ligand, and Plasma Microparticles after Human Immunodeficiency Virus Type 1 (HIV-1) Transmission: Implications for HIV-1 Vaccine Design

Abstract: The death of CD4؉ CCR5 ؉ T cells is a hallmark of human immunodeficiency virus (HIV) infection. We studied the plasma levels of cell death mediators and products-tumor necrosis factor (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 64 publications
0
88
0
3
Order By: Relevance
“…We have also shown that a clade B and a clade C CCR5-tropic Env can elicit high-avidity Ab with broad intraclade but not interclade specificity for incident Envs. We suggest that the induction of such Ab by HIV vaccines represents the induction of a nonneutralizing activity capable of contributing to virus control during the critical early period of HIV infection (13).…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that a clade B and a clade C CCR5-tropic Env can elicit high-avidity Ab with broad intraclade but not interclade specificity for incident Envs. We suggest that the induction of such Ab by HIV vaccines represents the induction of a nonneutralizing activity capable of contributing to virus control during the critical early period of HIV infection (13).…”
Section: Discussionmentioning
confidence: 99%
“…Even soluble FasL in serum from HIV-infected patients caused higher cell death of uninfected cells such as natural killer cells. 15 Elevated levels of immunosuppressive moieties in plasma such as TRAIL, FasL, and plasma microparticles can reduce or delay HIV-protective immune responses early after HIV infection 14 and also control responses to the vaccine itself. Plasmid DNA immunization of mice triggered a response by class II-restricted CD4 ϩ T cells that expressed FasL and killed the transfected antigenpresenting cells.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Loss of preexisting immunity would limit vaccine effectiveness irrespective of levels reached during the immunization period. Mechanisms for the destruction of preexisting immune cells likely involve both direct viral infection and indirect mechanisms such as the contact between uninfected immune cells bearing Fas receptors and cells bearing FasL.…”
Section: Introductionmentioning
confidence: 99%
“…TRAIL also induces apoptosis of infected cells. For example, plasma TRAIL has been reported to be an early pathogenic marker in acute HIV-1 infection and is correlated to viral load in chronic disease (Gasper-Smith, Crossman et al, 2008;Herbeuval, Nilsson et al, 2009). HIV-1 upregulates DR5 expression on the membrane of CD4 + T cells in vitro (Herbeuval, Boasso et al, 2005;Herbeuval, Grivel et al, 2005) making them prone to TRAIL-mediated apoptosis (Lichtner, Maranon et al, 2004).…”
Section: Atl and Trail-induced Apoptosismentioning
confidence: 99%